ASUHAN KEPERAWATAN PADA TN. H DENGAN GAGAL GINJAL KRONIK (GGK) DENGAN HEMODIALISIS DI RUANG HEMODIALISA RS. BHAYANGKARA TK. I R. SAID SUKANTO - Cinta Novanda Cahyarani (2022)
Background: Chronic Kidney Disease (CKD) is a progressive and irreversible decline in kidney function, causing uremia. Objective: This research was conducted to provide knowledge and real picture in providing nursing care to Chronic Kidney Disease patients by covering assessment, nursing diagnosis, nursing action plan, nursing implementation and nursing evaluation. Method: the design used is descriptive in the form of a case study to explore the problem of nursing care for Chronic Kidney Disease on Hemodialisis at Bhayangkara Tk.I Hospital R. Said Sukanto, data collection methods were carried out by interview, observation, physical examination and documentation study. Results: the nursing problems found in this case were excess fluid volume related to impaired regulatory mechanisms, ineffective breathing patterns related to respiratory muscle fatigue, activity intolerance related to an imbalance between oxygen supply and demand. After nursing actions for 1 x 4 hours, the results of the evaluation of two problem diagnoses were partially resolved and one problem diagnosis had not been resolved. Conclusion: it is hoped that further researchers can implement nursing care in patients with Chronic Kidney Disease properly and appropriately so that it is achieved in accordance with the problems found in patients